Cooperation patterns of high-tech companies in Shanghai and Beijing: accessing external knowledge sources for innovation processes - Liefner, Ingo; Zeng, Gang (ERDKUNDE, 2008)
The endowment of cities with sources of new knowledge, e.g. universities and innovative enterprises, creates opportunities for cooperation in innovation processes. This article analyzes to what extent the regional availability of such knowledge sources influences the cooperation patterns of enterprises in Shanghai and Beijing. The article contributes to the broader discussion of how technological progress in China’s leading metropolitan regions is influenced by economic and institutional changes. The empirical analyzes are based on statistically representative survey data. Thus, this article complements a number of related publications that are based on case study material. The analyses show that the availability of local knowledge providers explains the relative importance of knowledge sources but not the absolute frequency of contacts.